Evolutionary transition of doublesex regulation from sex-specific splicing to male-specific transcription in termites - Satoshi Miyazaki (Nature Portfolio, 2021)
Abstract The sex determination gene doublesex (dsx) encodes a transcription factor with two domains, oligomerization domain 1 (OD1) and OD2, and is present throughout insects. Sex-specific Dsx splicing isoforms regulate the transcription of target genes and trigger sex differentiation in all Holometabola examined to date. However, in some hemimetabolous insects, dsx is not spliced sexually and its sequence is less conserved. Here, to elucidate evolutionary changes in dsx in domain organisation and regulation in termites, we searched genome and/or transcriptome databases for the dsx OD1 and OD2 in seven termite species and their sister group (Cryptocercus woodroaches). Molecular phylogenetic and synteny analyses identified OD1 sequences of termites and C. punctulatus that clustered with dsx of Holometabola and regarded them as dsx orthologues. The Cryptocercus dsx orthologue containing OD2 was spliced sexually, as previously shown in other insects. However, OD2 was not found in all termite dsx orthologues. These orthologues were encoded by a single exon in three termites for which genome information is available; they were not alternatively spliced but transcribed in a male-specific manner in two examined species. Evolution of dsx regulation from sex-specific splicing to male-specific transcription may have occurred at an early stage of social evolution in termites.